1978
DOI: 10.1042/bj1730269
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent changes of intrinsic fluorescence of chemically modified liver alcohol dehydrogenases

Abstract: Horse liver alcohol dehydrogenase specifically carboxymethylated on cysteine-46 (a ligand to the zinc in the active site) or acetimidylated on 25 of the 30 lysine residues per subunit (including residue 228) was studied. The tryptophan fluorescence of these enzymes decreased by 35 % as pH was increased, with an apparent pKa of 9.8 + 0.2, identical with that of native enzyme. Native enzyme in the presence of 30mM-imidazole, which displaces a water molecule ligated to the zinc, also had a pKa of 9.8. The ionizab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
(28 reference statements)
3
26
0
Order By: Relevance
“…Fluorophores and chromophores were dissolved by shaking and stirring at room temperature under subdued lighting conditions using transparent solvents recommended by the suppliers. The pH was noted because the fluorescence properties of some molecules are pH‐dependent (49), and the solutions were then placed in 10 × 10 × 40 mm 3 UV quartz cuvettes (NSG Precision Cells, Inc., Farmingdale, NY). EEM data were collected immediately thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorophores and chromophores were dissolved by shaking and stirring at room temperature under subdued lighting conditions using transparent solvents recommended by the suppliers. The pH was noted because the fluorescence properties of some molecules are pH‐dependent (49), and the solutions were then placed in 10 × 10 × 40 mm 3 UV quartz cuvettes (NSG Precision Cells, Inc., Farmingdale, NY). EEM data were collected immediately thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…6) was responsible for the change in activity [53-55]. Various modifications of Lys-228 could affect the activity to different extents, and some modified enzymes were used for studies on the mechanism and pH dependencies of hydride transfer [56-60]. An X-ray structure determined at 3.2 Å for enzyme in which 23 of the 30 lysine residues per subunit were isonicotinimidylated showed that the apoenzyme was in the open conformation, and NADH could only be diffused into the crystals with low occupancy in the active site without causing the crystals to shatter [61].…”
Section: Modifications Of Amino Acid Residues That Affect Coenzyme Bimentioning
confidence: 99%
“…Several different kinetic mechanisms were examined, and the simplest mechanism that fits the data is shown in Scheme 3, where a rate-limiting deprotonation of the HE-NAD + complex ( k 2 , about 230 s −1 ) is coupled to the conformational change and occurs before the caprate binds. The initial deprotonation is coincident with changes in protein fluorescence and absorption at 280 nm, which seem to report on the protein conformation [60, 76, 77]. In this case, the kinetic “isomerization” is concluded to be equivalent to the structural “conformational change”.…”
Section: Ph Dependence Of Nad+ Binding and Isomerizationmentioning
confidence: 99%
“…In view of the above observations and considerations, it may be significant that the addition of trifluoroethanol, a substrate analogue (Shore et al, 1974), to the CmLADH-NAD+ complex produces a carboxylate chemical shift close to that of the NADH binary complex (Table III). As suggested by Parker et al (1978), the alcohol substrate is important for orienting the NAD+ coenzyme in the proper conformation necessary for catalysis in CmLADH, presumably one similar to that of NADH. Further insights into the mechanistic details of the enzyme could not, unfortunately, be obtained by studies of active site ionizations using this probe.…”
Section: Discussionmentioning
confidence: 98%
“…The carboxylate chemical shift has proven so far to be insensitive to pH changes in the active site in the presence and absence of some of the ligands. The nature of the proton-linked group(s) in the mechanism continues to elude identification, despite much intensive efforts (DeTraglia et al., 1977;Wolfe et al, 1977;Coates et al, 1977;Parker et al, 1978;Kvassman & Pettersson, 1978). Further structural studies of the active site are clearly needed, especially in view of the inherent ambiguities in the recent determination of the crystal structure of the holoenzyme in the presence of competent substrates (Plapp et al, 1978).…”
Section: Discussionmentioning
confidence: 99%